Krisis Literasi Dasar di Sekolah Dasar Indonesia: Konstruksi Pedagogis Guru dalam Menangani Siswa Kelas 3 yang Belum Lancar Membaca - Delima (STAI AL-AMIN, 2026)
The crisis of basic literacy in Indonesian elementary schools remains a serious issue affecting students’ learning processes. The phenomenon of third-grade students who are not yet fluent in reading indicates pedagogical challenges faced by teachers in early literacy instruction. This study aims to describe teachers’ pedagogical constructions in handling third-grade students with limited reading fluency and the strategies used to improve students’ basic literacy skills. This research employed a qualitative approach with a descriptive research design. Data collection techniques included observation, interviews, and documentation. The research subjects consisted of classroom teachers and elementary school students. The findings revealed that teachers developed pedagogical approaches through individualized learning, the use of simple reading media, reading habituation, and continuous learning motivation. In addition, parental involvement and the learning environment also influenced the improvement of students’ reading abilities. This study concludes that adaptive and humanistic pedagogical constructions play an important role in overcoming the crisis of basic literacy among elementary school students.